Association Between Socioeconomic Status and the Development of Asthma: Analyses of Income Trajectories - Kozyrskyj, A.; Kendall, Garth; Jacoby, P.; Sly, Peter; Zubrick, Stephen (American Public Health Association, 2010)
Am J Public Health. 2009 Aug 20. [Epub ahead of print]Association Between Socioeconomic Status and the Development of Asthma: Analyses of Income Trajectories.Kozyrskyj AL, Kendall GE, Jacoby P, Sly PD, Zubrick SR.University of Alberta.Objectives. Using data on 2868 children born in the Western Australian Pregnancy Cohort (Raine) Study, we examined the association between changes in family socioeconomic status and childhood asthma.Methods. We determined the likelihood (odds ratio) of a child having asthma at ages 6 and 14 years for 4 family-income trajectories (chronic low, increasing, decreasing, and never low) over the child's lifetime. The trajectories were created from longitudinal latent-class models.Results. We found a 2-fold increased risk of asthma at age 14 years among children who had lived in a low-income family since birth, especially for girls. Asthma was less likely to occur in children born to single parents; income rose over time in many of these families. Compared with children in chronic low-income families, children in households with increasing incomes had a 60% lower risk of asthma. Single-point measures of low income were not found to be associated with asthma.Conclusions. Chronic exposure to a low-income environment from birth was associated with the development of persistent asthma. There was also a protective effect against asthma among those children whose families had moved out of poverty.PMID: 19696386 [PubMed - as supplied by publisher